The Influence of Work Environment and Turnover Intention on Performance: Evidence From a Maritime Vocational Polytechnic - Transelasi, Fajar; Rohmah, Nur (Universitas Negeri Semarang, 2024)
This study aims to examine the effects of work environment and turnover intention on the performance of lecturers at Politeknik Ilmu Pelayaran Semarang. Limited research exists on work environment and turnover intention in the context of maritime vocational education, and inconsistencies in previous studies on turnover intention and lecturer performance further justify this investigation. Turnover intention is also crucial for identifying factors that influence an employee’s decision to stay with or leave the organization. This study employs a quantitative, causal approach to test the relationships between variables, with quantitative methods chosen for their generalizability within the maritime vocational education context. Due to the limited number of lecturers, a saturated sample of 30 respondents was used, all of whom were faculty members at Maritime Vocational Polytechnic. Data were analyzed using Variance-Based Structural Equation Modeling (VB-SEM). Findings indicate that both work environment and turnover intention have a positive and significant effect on lecturer performance. However, turnover intention does not mediate the relationship between work environment and performance, suggesting that other factors may shape performance outcomes. This implies that enhancing lecturer comfort and fostering a supportive work environment could further improve performance. Future research should explore factors underlying the positive influence of turnover intention on lecturer performance at PIP Semarang.